2020
DOI: 10.1002/jsp2.1118
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic vertebral morphology in normal and scoliosis deformity in skeletally immature rabbits: A Longitudinal study

Abstract: Objective: To measure age-related changes in thoracic vertebral body heights (VBH) in skeletally immature normative and scoliotic rabbits to assess how VBH change during growth. To examine the potential link between the moment-arm of the rib tether and vertebral wedging as well as the sum of the curvature angles at the apical level (T7). To assess the correlation between the magnitude of initial spine curve and final spine curve in the scoliotic group. Methods: Eight healthy, skeletally immature normative New … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…An alternative means to induce asymmetric vertebral growth (and scoliosis) is unilateral rib tethering, which provides asymmetric longitudinal compression to vertebrae, altering the stress distribution. Alfraihat et al 20 used unilateral rib tethering in skeletally immature rabbits (age: 7-28 weeks) and reported a 5% reduction of T7…”
Section: Asymmetrical Longitudinal Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…An alternative means to induce asymmetric vertebral growth (and scoliosis) is unilateral rib tethering, which provides asymmetric longitudinal compression to vertebrae, altering the stress distribution. Alfraihat et al 20 used unilateral rib tethering in skeletally immature rabbits (age: 7-28 weeks) and reported a 5% reduction of T7…”
Section: Asymmetrical Longitudinal Growthmentioning
confidence: 99%
“…19 A study on immature rabbits found that T7 vertebral body height averaged 20 microns/day from ages 7 to 28 weeks. 20 In comparison, T1-T12 vertebral body heights in normative pediatric human subjects had considerably slower growth rates, ranging from 1.9 to 3 microns/ day. 21 Caudal vertebral (Cd7) growth plates of late-adolescent rats grow longitudinally at 30 microns/day, while proximal tibial growth plates of earlier-adolescent rabbits grow at a rate of 366 microns/day.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Thoracic curves are more likely to progress than lumbar curves because of the inherent stiffness associated with the presence of the rib cage [ 30 , 31 ], and double major curves are more likely to progress than single curves [ 23 , 34 ]. Wedging of the intervertebral disc and adjacent vertebrae are also factors associated with severe spine curvature [ 5 , 24 , 29 , 35 37 ]. However, attempts to use each of these features individually as a prognostic factor for curve progression showed inaccurate (i.e., a high number of false positive and false negative) predictions [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also been performed on functional neuroanatomy of the domestic rabbit (Osofsky et al, 2007). Alfraihat et al (2020) studied thoracic vertebral morphology in normal and scoliosis deformity in skeletally immature rabbits: In longitudinal study, they examined changes in the VBH (vertebral body height).…”
Section: Introductionmentioning
confidence: 99%